2021
DOI: 10.1186/s13690-021-00660-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm prevalence and associated factors among street children in Mashhad, North East of Iran

Abstract: Background Self-harm is intentional harmful behavior in the context of emotional distress. Street children are boys and girls under eighteen who are forced to work or live on the streets. These children are exposed to violent situations and high-risk behaviors like self-harm. This study investigated the prevalence of self-harm in street children in Mashhad, the second Metropolis of Iran. Methods In this cross-sectional study, 98 children were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 26 studies reported the prevalence of HIV, HBV, HCV, drug use, opium, cannabis, alcohol, tobacco smoking, sexual abuse, and sexual contact in street children, but eight studies reported duplicate data, and we removed these studies. Finally, 18 studies were included in this systematic review and meta‐analysis, 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 (Roshanfekr et al, unpublished) (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies reported the prevalence of HIV, HBV, HCV, drug use, opium, cannabis, alcohol, tobacco smoking, sexual abuse, and sexual contact in street children, but eight studies reported duplicate data, and we removed these studies. Finally, 18 studies were included in this systematic review and meta‐analysis, 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 (Roshanfekr et al, unpublished) (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 16 In some studies, no significant relationship was found between the route of administration of opium and stone size, 23 while some studies suggested that oral opium consumption is significantly associated with the size of bile duct stones. 24 , 25 Further studies are highly recommended to investigate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the SF3B1 variant recognizes a different branch point, altering splicing patterns in uveal melanoma and lymphocytic leukemia (5,6). Splicing variants in cancer have also been reported to generate various cancer antigens (7,8), which play a crucial role in predicting the prognosis of various types of cancer, including breast and gastric cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%